Addressing the Challenge of Ineffective Airway Clearance in Toddler-Aged Children: The Role of Chest Physiotherapy in Arjawinangun Hospital - Yulianti S, Ayu; Zaitun, Zaitun; Mafikasari, Febiyanti (Ann Publisher, 2024)
The health problems often experienced by toddler-age children are the respiratory system, with nursing problems, namely ineffective airway cleaning caused by bacteria, viruses, fungi, and protozoa that infect the lungs. Handling ineffective airway cleaning nursing problems in children can be done by medical and nursing measures, including chest physiotherapy. Objectives: To describe the implementation of chest physiotherapy measures, define the response and results of chest physiotherapy, and analyze the difference in outcomes in two pediatric patients with ineffective airway clearance performed by chest physiotherapy. Methods: A comparative descriptive research design will be used to compare two subjects with the same criteria and conditions. Results: After five days of intervention, there was a difference in response in the two subjects; namely, airway clearance in subject one could be resolved with four indicators: sputum, rakhi, dyspnea, and respiratory rate. In subject 2, it could be partially resolved with 2 indicators that were resolved, namely dyspnea and respiratory rate, and this intervention was by the nursing problem that was enforced. Conclusion: The application of chest physiotherapy in toddler children can provide improvements in sputum, dyspnea, Ronchi, and respiratory rate within normal limits.